The Metabotropic Glutamate Receptor MGL-2 gates satiety by modulating Serotonergic Signaling in C. elegans - Lacour, Ailin (2025)
How neural circuits encode internal nutrient states to generate adaptive behaviors is a fundamental question in neuroscience. In this study, we explore the mechanisms through which C. elegans perceives its nutritional state and adjusts feeding and locomotor behaviors. We show that mutants of mgl-2, the C. elegans ortholog of mammalian metabotropic glutamate receptors (mGluRs), exhibit hyperphagia and decreased locomotion—phenotypes reminiscent of hungry animals, even in the absence of food deprivation. This excessive feeding results in elevated lipid accumulation, underscoring the critical role of MGL-2 in promoting satiety. In wild-type animals, food encounter after starvation induces a pronounced serotonin release that facilitates feeding and suppresses locomotion to promote nutrient recovery. Using genetic approaches and in vivo neuronal imaging, we demonstrate that MGL-2 is essential for the perception of nutritional status and for regulating serotonergic signaling in fed animals. Ongoing work aims to identify the specific neuronal circuits in which MGL-2 operates. Our findings support a model in which MGL-2 acts as a key modulator within neural pathways governing appetite and energy balance. Notably, mammalian mGluRs have recently been linked to hunger and satiety perception, suggesting evolutionary conservation in these regulatory mechanisms. This study provides insights into the neurobiological basis of feeding behavior with potential relevance across species.